Kupffer cells activation promoted binge drinking-induced fatty liver by activating lipolysis in white adipose tissues. (1st September 2017) - Zhao, Yu-Ying; Yang, Rui; Xiao, Mo; Guan, Min-Jie; Zhao, Ning; Zeng, Tao
Graphical abstract: Highlights: GdCl3 and etanercept attenuated binge drinking-induced hepatic TG accumulation by a similar amount. GdCl3 and etanercept had no effects on ethanol-induced disturbance of PPAR-α and SREBP-1c. GdCl3 and etanercept suppressed binge drinking-induced phosphorylation of HSL. TNF-α promoted HSL phosphorylation and lipolysis in cultured epididymal adipose tissues. Abstract: Kupffer cells (KCs) have been suggested to play critical roles in chronic ethanol induced early liver injury, but the role of KCs in binge drinking-induced hepatic steatosis remains unclear. This study was designed to investigate the roles of KCs inhibitor (GdCl3 ) and TNF-α antagonist (etanercept) on binge drinking-induced liver steatosis and to explore the underlying mechanisms. C57BL/6 mice were exposed to three doses of ethanol (6 g/kg body weight) to mimic binge drinking-induced fatty liver. The results showed that both GdCl3 and etanercept partially but significantly alleviated binge drinking-induced increase of hepatic triglyceride (TG) level, and reduced fat droplets accumulation in mice liver. GdCl3 but not etanercept significantly blocked binge drinking-induced activation of KCs. However, neither GdCl3 nor etanercept could affect binge drinking-induced decrease of PPAR-α, ACOX, FAS, ACC and SCD protein levels, or increase of the LC3 II/LC3 I ratio and p62 protein level. Interestingly, both GdCl3 and etanercept significantly suppressed binge drinking-induced phosphorylation of HSL in epididymal adipose tissues. Results of i n vitro studies with cultured epididymal adipose tissues showed that TNF-α could increase the phosphorylation of HSL in adipose tissues and upgrade the secretion of free fatty acid (FFA) in the culture medium. Taken together, KCs inhibitor and TNF-α antagonist could partially attenuate binge drinking-induced liver steatosis, which might be attributed to the suppression of mobilization of white adipose tissues. These results suggest that KCs activation may promote binge drinking-induced fatty liver by TNF-α mediated activation of lipolysis in white adipose tissues.